Integration of Aroma and Savour for Tourism to Entreat the Tourists in Rajasthan: A Socio Analytical Study - Monika Rani, Shikha Sharma, Mahesh Uniyal (International Journal of Advanced Science and Technology, 2020)
The tourism industry is one of the prime segments for the growth and revenue elevation in any country. Rajasthan is one of the key tourist destinations in India. As per the reports from India Today, the Rajasthan State achieved more than 21 percent rise in visitors in last year with more than 5 crore tourists. The food and local cuisine of Rajasthan is having the flavor of tang and local aroma in which the health based food is prepared so that the environmental conditions can be met and there will be safeguard of the human health. The Rajasthani culture is having enormous food and cuisines in which the taste and tang perspectives are integrated. In this manuscript, the analytics on the Rajasthani food with the evolution as well as adoption of local food is presented. The tourists from assorted locations and legends are analyzed in terms of their taste and tang with the specific factors towards visiting Rajasthan. It is found from the research aspects and analytics that the local cuisine is gaining huge prominence and attracting the tourists from multiple regions and that is elevating the overall performance and revenue of Rajasthan state as well as the cumulative revenue of the country. Keywords: Rajasthani Food, Taste and Tang, Revenue, Region